2015
DOI: 10.1002/jrs.4720
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics of Al‐containing MAX‐phase carbides: a first‐principle study

Abstract: A systematic study on lattice dynamics of M n + 1 AlC n (n = 1-3) phases using first-principle calculations is reported, where the Raman-active and infrared-active (IR) modes are emphasized. The highest phonon wavenumber is related to the vibration of C atoms. The 'imaginary wavenumber' in the phonon spectrum of Nb 3 AlC 2 contributes to the composition gap in Nb-Al-C system (Nb 2 AlC and Nb 4 AlC 3 do appear in experiments, but there are no experimental reports on Nb 3 AlC 2 ). The full set of Ramanactive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 79 publications
2
19
0
Order By: Relevance
“…1b, c. In both e-and m-structures, phonon band gaps are observed. The PPDOS of C atoms locate mainly above the gap, and PPDOS of Mo and Ga atoms are in lower energy range, which is consistent with the common features found in phonon spectra of other MAX phases [41][42][43]. However, noticeable difference in PPDOS for Ga atoms of two structures is observed.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…1b, c. In both e-and m-structures, phonon band gaps are observed. The PPDOS of C atoms locate mainly above the gap, and PPDOS of Mo and Ga atoms are in lower energy range, which is consistent with the common features found in phonon spectra of other MAX phases [41][42][43]. However, noticeable difference in PPDOS for Ga atoms of two structures is observed.…”
Section: Resultssupporting
confidence: 88%
“…However, noticeable difference in PPDOS for Ga atoms of two structures is observed. A Ga-PPDOS peak appears around 8 THz in e-structure, but it shifts to lower frequency (about 5 THz) in m-structure, implying Ga atoms in e-structure are more strongly bound than those in m-structure [41]. Most importantly, unlike in the zig-zag structure where imaginary frequency modes appear apparently [11], in Fig.…”
Section: Resultsmentioning
confidence: 72%
“…Zr 2 AlC and Zr 3 AlC 2 were screened as stable MAX phases by Aryal et al according to the elastic and thermodynamic stability. Bai et al also confirmed the dynamic stability of Zr 2 AlC and Zr 3 AlC 2 by exhibiting their calculated phonons having no imaginary wave number. Last year, Lapauw et al synthesized Zr 2 AlC and Zr 3 AlC 2 by means of reactive hot pressing of a ZrH 2 , Al and C powder mixture.…”
Section: Introductionmentioning
confidence: 83%
“…The deficiency of the knowledge about these nanolaminates’ properties greatly limits the practical application of these materials. Density functional theory (DFT), as an essential research tool in material field, has gained a series of achievements in the exploration of MAX phase and predicted plenty of properties . However, the investigations on the Zr–Al–C system are still deficient.…”
Section: Introductionmentioning
confidence: 99%
“…Bai et al . carried out a first principles studys of the lattice dynamics of Al‐containing MAX‐phase carbides . Lambruschi and co‐workers reported a study of the Raman spectroscopy of CaM 2+ Ge 2 O 6 (M 2+ = Mg, Mn, Fe, Co, Ni, Zn) clinopyroxenes .…”
Section: Solid‐state Studiesmentioning
confidence: 99%